2021
DOI: 10.1080/13651501.2021.1951294
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and predictors of non-response in severe catatonic patients treated with electroconvulsive therapy

Abstract: To explore the demographic and clinical features of severe catatonic patients, comparing responders and non-responders to ECT in order to detect possible predictors of non-response. METHODSThis naturalistic study included 59 catatonic inpatients with a diagnosis of mood disorder according to DSM-IV-TR criteria. All patients were treated with bilateral ECT and evaluated before and after ECT course. The response to ECT was defined as a Clinical Global Impression (Improvement subscale) rating 1 "very much improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…The impressive effectiveness of ECT in the treatment of catatonia, with a response rate of 95%, parallels previous reports 13 16 17 21 22 23 26 . One catatonia study reported lower response rates to ECT at 59% 25 .…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The impressive effectiveness of ECT in the treatment of catatonia, with a response rate of 95%, parallels previous reports 13 16 17 21 22 23 26 . One catatonia study reported lower response rates to ECT at 59% 25 .…”
Section: Discussionsupporting
confidence: 89%
“…The strength of the study is its sample, which includes a large proportion of severely ill patients with catatonia and schizophrenia (90 %) as the underlying mental disorder. Most recent studies examining the effectiveness of ECT included mixed samples with patients with unipolar or bipolar depression and only a small proportion of patients with schizophrenia [11,26,50]. The patients in our sample were well-characterized and received multiple sessions of ECT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of at least two symptoms on this scale allows the hypothesis of catatonia to be made [9]. A total score above 30 indicates severe symptomatology, as confirmed by studies or other observations [20,21].…”
Section: Discussionmentioning
confidence: 95%
“…Since Leroy et al’s review, four additional studies of ECT with pre/post-quantitative outcomes have been published ( Perugi et al, 2017 ; Pierson et al., 2021 ; Tor et al, 2021 ; Tripodi et al, 2021 ). All were naturalistic case series or retrospective analyses, using Clinical Global Impression (CGI) or BFCRS quantitative outcomes.…”
Section: Treatmentmentioning
confidence: 99%